Loss‐Driven Systems Engineering and Siloism. Issue 4 (11th January 2021) - Jackson, Scott
ABSTRACT: This article discusses the siloism concept in LDSE and the use of the integrated product team (IPT) concept to mitigate it. Siloism is any project team member's unwillingness to share information especially to mitigate conflicts and overlaps among project specialties. Failure to mitigate siloism potentially reduces the entire project's effectiveness. A recognized siloism mitigation method is employing the IPT concept. This concept uses organizational structure and rigorous management combined to encourage spcialty information sharing. Aligning the organizational project structure to the physical system architecture seeks close specialty cooperation. IPTs are part of the larger concept called Integrated Product and Process Development (IPPD) described in INCOSE's work (2015, 199‐203).